New Entrant Strategy: Market Entry and Competition with an Arch Incumbent - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2007)
By definition, de novo industry ventures do not share many market-contact points with incumbents – itself an important source of competitive ‘stability’ through mutual forbearance. As such, these ventures are often subject to aggressive retaliation at the outset, which could threaten their very survival. While a large market overlap with a single established incumbent (the ‘arch-incumbent’ to a new entrant) is not conducive to survival in general, there is a special exception for ventures with sufficient entry resources and scale to rapidly increase efficiency and to signal deep financial resources to withstand retaliation. The empirical experience of de novo entrants to the intra-European passenger air travel industry supports this notion. In particular, this intricate effect between entry capacity and market overlap with the arch-incumbent on venture survival overshadows the impact of a low-cost market positioning and other possible competitive advantages over incumbents that pre-dated the industry liberalization.